Medical Flight Emergencies and Bias: #thatisbias #whatadoctorlookslike #ILookLikeaDoctor (Mary Ann Liebert, 2020)
One in 604 flights will have a medical emergency. With 87,000 flights per day in the United States alone, that is ?144 medical emergencies per day. When a passenger has a medical emergency in-flight, do staff respond with equity to persons who offer assistance? Unfortunately, several news stories have highlighted race and gender bias against woman physicians of color who come to the aid of a person in distress while in-flight. Three separate stories have ignited a national conversation about what it means to ?look like a doctor.? In this article, we profile three vignettes of women physicians of non-white race that challenges the notion that all doctors are treated equally when trying to assist passengers who are experiencing a medical in-flight emergency. We share stories of how bias has affected other health care providers in similar situations. Some physicians have not been asked anything but their name, whereas others are questioned for their credentials before they can assist. In other vignettes, even with valid credentials, these offers of assistance from physicians are rebuked. We will challenge the aviation industry to put passengers first by training flight crews to see and address implicit and explicit biases, standardize protocols to remove barriers for assistance, challenging the notion of paperwork superseding care, and changing a very broken process that is inconsistent at best.